Fraud Risk Mitigation through the Integration of Hindu Values: Evidence from the Village Credit Institution (LPD) of Kesiman - Ni Luh Putu Uttari Premananda; Ni Made Rai Kristina; Putu Riska Wulandari; Astrid Krisdayanthi; Putu Ossi Widiari; Md. Yudyantara Risadi; I Made Indra Widiatmika (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Fraud in community-based financial institutions like Lembaga Perkreditan Desa (LPD) is a serious threat to governance and financial integrity. This study examines how Hindu values are included in fraud risk management at LPD Kesiman. We used a qualitative descriptive approach and gathered data through interviews with managers, supervisors, and community leaders, supported by relevant documents. Following the COSO Fraud Risk Management Framework (2023), the findings show that integrating Tattwa (the belief in God as moral accountability), Susila (ethical conduct as internal control), and Upacara (rituals that promote collective honesty) greatly strengthens the fraud mitigation framework. The originality of this study lies in proposing a model that incorporates Hindu values into fraud risk management as a form of local wisdom, a topic that is rarely addressed in the literature. This shows that preventing fraud in community financial institutions requires both technical methods and the internalization of cultural and spiritual values.